Immersive Experience Model of the Elderly Welfare Centers Supporting Successful Aging - Lee, Eun J.; Park, Sung J. (Frontiers in Psychology, 2020)
This study investigates the application of immersive experience services to leisure facilities for the successful aging of the elderly. In the past, the social image of the elderly was that of passive beings who needed care due to physical and cognitive decline associated with biological aging. However, the concept of “successful aging” actively highlighting the positive aspects of aging and trying to promote longer and healthier life, has started to acquire importance in recent years. In this context, elderly welfare centers can be described as facilities that encourage learning, leisure, and social activities of the elderly with impaired physical and cognitive functions. The use of recent immersive experience technologies such as Virtual Reality and Mixed Reality (MR), in order to mitigate physical and spatial constraints, and provide an immersion into the desired environment and situation, could contribute substantially to the health of the elderly. However, the application of immersive technologies is concentrated on the provision of entertainment, education, and medical facilities. The number of previous studies on the immersion experiences of the elderly is limited, and the connection between immersion experiences and various services and programs that promote successful aging at elderly welfare centers requires further research. This study analyzes the function and space of the elderly welfare centers for successful aging through the review of previous studies and classifies immersion technology categories based on the review of the relevant literature. The study analyzes the health benefits of immersive experience technologies and related products and services, and proposes an immersive experience service model for the elderly welfare center. The results of the study could provide a valuable input for the spatial application of immersive experience technologies for successful aging in the future.